Interview with Dr Briony Labram, Private Secretary in the UK Government’s Department of Science Research and Innovation - Poppy Gethin-Jones (BioScientist: The Salford Biomedicine Society Magazine, 2024)
One of the most exciting things about a degree in Biomedical Sciences and closely related degrees is that it can lead to a wide range of career options. Previous issues of Bioscientist magazine have explored well-known and popular biomedicine-aligned careers. In this issue, a career working for the government will be explored. Dr Briony Labram delves into an unusual graduate destination. Poppy Gethin-Jones secured an interview with Dr Labram, who after successfully completing a degree in Biology, went on a career journey that took her to the UK Government’s Department of Science Research and Innovation.
Keywords: Department of Science Research and Innovation; Private Secretary; UK Government; career prospects; biomedicine aligned careers; academic and industry expertise; National Technology Advisers; civil service